Self Compassion pada Peserta Didik Korban Perundungan di Madrasah Tsanawiyah Negeri Kota Bandung - Adara Puti Amani; Eni Nuraeni Nugrahawati (Bandung Conference Series: Psychology Science, 2024)
Abstract. There are many negatif impacts experienced by the victims of bullying. Being a victim of bullying, especially mocking on physical conditions can leads to sadness, anger, having low self-esteem, and even self hate. To reduce or overcome the stress, depression, and negatif emotions felt by victims of bullying, the victims must first show concern and understanding for themselves while facing problems or pressures that occur, and develop a positive manner towards unpleasant situations by fostering empathy for themselves, which in psychology, such an act is named as self compassion. The aim of this research is to determine the description of self compassion in students who experience bullying at MTsN Bandung. The measuring instrument used in this research is the Self compassion Scale for Youth (SCS-Y), which has been translated into Indonesian by Amaliah et al. (2024). The results of this research showed that students who were victims of bullying at MTs Negeri Bandung had high self compassion as many as 95 (59%) students and those who had low self compassion were 67 (41%) students. In the aspect of self kindness, 127 (28%) victims were in the high category, in the aspect of common humanity, 98 (60%) victims were in the high category, and in the aspect of mindfulness, 118 (73%) victims were in the high category. Abstrak. Banyak dampak buruk yang dialami oleh korban perundungan, terutama yang menyinggung kondisi fisik yang membuat remaja menjadi sedih, marah, rendah diri, bahkan korban dapat membenci dirinya sendiri. Untuk meminamilisir atau mengatasi stres, depresi, serta emosi negatif yang dirasakan korban perundungan, korban harus terlebih dahulu peduli dan memahami diri dengan menumbuhkan empati terhadap diri sendiri, dalam psikologi hal ini disebut dengan self compassion. Tujuan penelitian ini untuk melihat gambaran self compassion pada peserta didik yang mengalami perundungan di MTsN Kota Bandung. Metode yang digunakan dalam penelitian ini adalah studi deskriptif dengan subjek penelitian sebanyak 162 peserta didik korban perundungan di MTsN Kota Bandung. Alat ukur yang digunakan Skala Self Compassion Scale for Youth (SCS-Y) yang telah diadaptasi oleh Amaliah et al. (2024). Hasil penelitian ini adalah peserta didik korban perundungan di MTs Negeri Kota Bandung memiliki self compassion yang tinggi sebanyak 95 (59%) peserta didik dan yang memiliki self compassion rendah sebanyak 67 (41%) peserta didik. Pada aspek self kindness sebanyak 127 (28%) korban kategori tinggi, pada aspek commun humanity sebanyak 98 (60%) korban kategori tinggi, dan pada aspek mindfulness 118 (73%) korban kategori tinggi.